Risk Factors for Eye Diseases. Importance of Prevention - Armando Rafael Milanés Armengol; Katia Molina Castellanos; Marla Milanés Molina; Ángel Miguel Ojeda Leal; Alina González Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
The increased incidence of eye diseases is multifactorial in origin since risk factors related to the individual, environment, and solar radiation contribute to their development. The retina absorbs millions of photons of ultraviolet and blue light, which cause greater phototoxicity and irreversible damage. It is essential to study the pathogenesis of eye diseases and analyze the interaction of light with the eyes in depth. Eye disease prevention based on a personalized approach is critical to provide correct information, contribute to self-monitoring, and conduct a frequent medical follow-up. Continuous development of technology in the field of ophthalmic optics offers new perspectives for prevention. The aim of this review is to provide an update on this topic that can be used for training medical students and primary care physicians.